Relevant international law relating to treaties - Hamid, Abdul Ghafur@Khin Maung Sein (2016)
This is a power point presentation made at the Workshop on “Drafting of International Instruments: All You Need to Know” on 3 August 2016 at Dewan Tan Sri Abdul Kadir Yusof, Attorney General’s Chambers, Putra Jaya. It was attended by officers from various Government Ministries of Malaysia, including counsels from AGC. The main objective is to familiarize the participants with the fundamental principles of treaty-making, treaty interpretation and the validity of treaties.